Evidence for shared genetic risk factors between lymphangioleiomyomatosis and pulmonary function. Issue 1 (24th January 2022) - Farré, Xavier; Espín, Roderic; Baiges, Alexandra; Blommaert, Eline; Kim, Wonji; Giannikou, Krinio; Herranz, Carmen; Román, Antonio; Sáez, Berta; Casanova, Álvaro; Ancochea, Julio; Valenzuela, Claudia; et al.
Introduction: Lymphangioleiomyomatosis (LAM) is a rare low-grade metastasising disease characterised by cystic lung destruction. The genetic basis of LAM remains incompletely determined, and the disease cell-of-origin is uncertain. We analysed the possibility of a shared genetic basis between LAM and cancer, and LAM and pulmonary function. Methods: The results of genome-wide association studies of LAM, 17 cancer types and spirometry measures (forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC), FEV1 /FVC ratio and peak expiratory flow (PEF)) were analysed for genetic correlations, shared genetic variants and causality. Genomic and transcriptomic data were examined, and immunodetection assays were performed to evaluate pleiotropic genes. Results: There were no significant overall genetic correlations between LAM and cancer, but LAM correlated negatively with FVC and PEF, and a trend in the same direction was observed for FEV1 . 22 shared genetic variants were uncovered between LAM and pulmonary function, while seven shared variants were identified between LAM and cancer. The LAM-pulmonary function shared genetics identified four pleiotropic genes previously recognised in LAM single-cell transcriptomes: ADAM12, BNC2, NR2F2 and SP5 . We had previously associated NR2F2 variants with LAM, and we identified its functional partner NR3C1 as another pleotropic factor. NR3C1 expression was confirmed in LAM lung lesions. Another candidate pleiotropic factor, CNTN2, was found more abundant in plasma of LAM patients than that of healthy women. Conclusions: This study suggests the existence of a common genetic aetiology between LAM and pulmonary function. Pleiotropic molecular factors influencing LAM development and pulmonary function https://bit.ly/3AE3KgJ